Stem cell procedures in arthroscopic surgery. Issue 1 (December 2016) - Dyrna, Felix; Herbst, Elmar; Hoberman, Alexander; Imhoff, Andreas; Schmitt, Andreas
Abstract The stem cell as the building block necessary for tissue reparation and homeostasis plays a major role in regenerative medicine. Their unique property of being pluripotent, able to control immune process and even secrete a whole army of anabolic mediators, draws interest. While new arthroscopic procedures and techniques involving stem cells have been established over the last decade with improved outcomes, failures and dissatisfaction still occur. Therefore, there is increasing interest in ways to improve the healing response. MSCs are particularly promising for this task given their regenerative potential. While methods of isolating those cells are no longer poses a challenge, the best way of application is not clear. Several experiments in the realm of basic science and animal models have recently been published, addressing this issue, yet the application in clinical practice has lagged. This review provides an overview addressing the current standing of MSCs in the field of arthroscopic surgery. Level of evidence IV.